Limits of equisymmetric $1$-complex dimensional families of Riemann surfaces - Costa, Antonio F.; González-Aguilera, Víctor (MATHEMATICA SCANDINAVICA, 2017)
We describe the limit surfaces of some equisymmetric $1$-complex dimensional families of Riemann surfaces in the boundary of the Deligne-Mumford compactification of moduli space. We provide a description of such nodal Riemann surfaces in terms of the group of automorphisms defining the family. We apply our method to some known examples.